Features of Soret and Dufour effects on an unsteady mixed convection nanofluid flow about a revolving Riga cone - T. A. Yusuf; S. O. Salawu; U. D. Akpan (International Journal of Thermofluids)
Temperature, concentration, and composition gradients may all produce mass and energy fluxes when heat and mass transfer occur concurrently in a flowing fluid. This has ramifications for several industries, including aircraft and thermal engineering. The present study focuses on the numerical modelling of an Ag-kerosene oil nanofluid spinning in a rotating cone with time-dependent angular velocities affected by heat and mass diffusion. The cone Riga surface creates an external electric field that causes the wall to paralleled Lorentz force, which regulates the nanofluid flow. The effects on the heat and mass distributions of the diffusion-thermo (Dufour) and thermal-diffusion (Soret) are all considered. Similarity analysis yields a non-dimensional system of ODEs, and the shooting technique with the Runge-Kutta-Fehlberg scheme is then used to carry out the simulation. Graphs are used to illustrate the parametric analysis of the different flow profiles and the validation with the existing study is demonstrated with a strong connection in this specific scenario. It is observed that the flow dynamics were affected by the spinning Riga cone shape that generates centrifugal forces, which result in complicated thermal dispersion and flow pattern features.